2003
DOI: 10.1108/09578230310464657
|View full text |Cite
|
Sign up to set email alerts
|

Administrative problem solving in the information age

Abstract: The information age is upon us. In schools across the country, administrators are making important decisions about how best to employ computer technology. This case study of an expert educational administrator looks at computer use from a problem‐solving perspective, focusing on the relationship between how this school leader thinks about and acts on technological capacity. It examines the personal attributes and perceptions that underlie his effective application of technology and finds them interwoven with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Despite efforts to establish the discipline of educational administration as a cognitive domain that defines expertise and effectiveness in terms of problem-solving processes (Perez & Uline, 2003), tacit knowledge understanding (Nestor-Baker & Hoy, 2000), or mental models (Ruff & Shoho, 2005), there remains a large gap in the literature regarding cognitive aspects and school administration (Da’as et al, 2018; Kara & Ertürk, 2015). Researchers have argued for the need to understand the cognitive processes of school leaders, suggesting studies on the influence of leaders’ cognitive processes on school effectiveness (Kara & Ertürk, 2015; Ruff & Shoho, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to establish the discipline of educational administration as a cognitive domain that defines expertise and effectiveness in terms of problem-solving processes (Perez & Uline, 2003), tacit knowledge understanding (Nestor-Baker & Hoy, 2000), or mental models (Ruff & Shoho, 2005), there remains a large gap in the literature regarding cognitive aspects and school administration (Da’as et al, 2018; Kara & Ertürk, 2015). Researchers have argued for the need to understand the cognitive processes of school leaders, suggesting studies on the influence of leaders’ cognitive processes on school effectiveness (Kara & Ertürk, 2015; Ruff & Shoho, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to leadership preparation, Perez and Uline (2003) urged aspiring administrators to immerse in the problem-solving processes: JEA 49,2…”
Section: Switching Cognitive Gearsmentioning
confidence: 99%
“…The absence of statistically significant relationships found in this research study challenge the results of previous research. Earlier research found a relationship between leadership style and computer use (Brown, 1996;Dooley, 1995;Murphy, 1998;Perez, 1999;Sosik, 1995;Vacca, 1984). Surinder, Sosik and Avolio (1997) also reported support for a relationship between technology use and leadership style.…”
Section: Discussionmentioning
confidence: 97%
“…Vacca (1984) determined that school principals who made the most successful utilization of computers in educational settings were those who scored high in both initiating structure and consideration. Educational administrators who were identified as having a leadership style that was high in consideration behavior were found to be the most successful at achieving instructional change (Murphy, 1998;Perez, 1999). Surinder, Sosik and Avolio (1997) reported that structured problems with technology were more likely to be solved with an initiating style.…”
Section: Leadership Stylementioning
confidence: 99%
See 1 more Smart Citation